ANALISIS PENGARUH PERENCANAAN PAJAK, BEBAN PAJAK KINI DAN BEBAN PAJAK TANGGUHAN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN OTOMOTIF YANG TERDAFTAR DI BEI PERIODE 2015-2019 - Deviyarty, Serly; Shinta Lestari, Deara; Panjaitan, Fery (Jurnal Akuntansi Bisnis Dan Keuangan, 2021)
The research was conducted from September 2020 to February 2021 at automotive companies listed on the Indonesia Stock Exchange.The main motivation for conducting the research with the title Analysis of the Effect of Tax Planning, Current Tax Expenses and Deferred Tax Expenses on Earnings Management in Automotive Companies Listed on the Indonesia Stock Exchange for the 2015-2019 Period because tax is the largest source of state revenue, but there are differences in interests between the government and companies. related to taxes. For companies, the tax burden can reduce net income so as to encourage companies to reduce the tax burden as small as possible which ultimately affects state revenues. In many companies the tax burden can affect earnings management activities.Analytical methods used multiple linear regression analysis, hypothesis testing ( test T and test F) and coefisient of Determination. Regression equation for earnings management = -20,767 + 0.321 tax planning – 0,376 current tax expense + 4,140 deffered tax expense. Hypothesis testing as a whole (Test F) can be seen that tax planning, current tax expense and deferred tax expense. simultaneously has a significant effect on earnings management with significant level 0,039. Partialily using (Test T) proves that tax planning has a significant effect on earnings management with significant level 0,006. Current tax expense has no significant effect on earnings management with significant level 0,403. Deferred tax expense has no significant effect on earnings management with significant level 0,496. Coefficient of Determination (R2) adjusted on regression model obtained 0,399. The conclusion in this study is that the tax planning carried out by the company is followed by the practice of profit management so that the company’s profit reaches an optimal level, there is no opportunity for management to carry out earnings management because the current tax burden is imposed based on the amount of taxable income multiplied by the corporate income tax rate. has limitations in influencing the size of the company’s deferred tax burden, because there are regulations regarding deferred tax expense in commercial accounting and fiscal accounting which are regulated by taxation laws and regulations, the amount of tax burden that must be paid by the company encourages the practice of earnings management with the aim of obtaining net income optimal.Suggestions to the next researcher are to add research variables, replace research objects, and increase the research period.